Estudo envolvendo atividades de matemática na perspectiva do "pensar rápido e devagar" / Ivan Talian. - Talian, Ivan (2024)
This study arises from the problem related to the difficulty that students have in solving problem situations that involve more complex thoughts, especially those associated with the Mathematics curricular component, present in Basic Education. To this end, it starts from the discussions brought by Daniel Kahneman in the work "Thinking, Fast and Slow", published in 2011, and proposes activities that give students the opportunity to "think about their way of thinking". In this work, the author, based on scientific studies developed in the field of cognitive and behavioral psychology, highlights how our brain works with two ways of thinking, one intuitive (fast) and the other deliberative and with a greater degree of awareness (slow), showing how we can easily be manipulated by our intuitive thinking and make a decision that, at times, is not the most appropriate. This perspective defines the following question as the central question of the study: How can the inclusion of problem situations considered conflicting in Mathematics teaching help students identify the existence of different ways of thinking? Conflict situations are understood as those that often lead people to respond intuitively, without realizing certain traps and that would need to be responded to more slowly, involving reasoning and attention. The objective of this study is to structure, apply and evaluate a set of activities associated with Mathematics content that enable the solution to elucidate the systems of thought announced by Daniel Kahneman in his work "Thinking, Fast and Slow". Aiming to answer the main question and achieve the stated objective, the study discusses the difference between these two ways of thinking, highlighting their importance for everyday life, although it seeks to highlight what Kahneman (2011) calls "System 2", associating it with conscious, deliberative and, in this study, considered reflective thinking. The activities developed cover different mathematical content found in textbooks or similar to them, situations present in students' daily lives and that involve knowledge especially of financial mathematics and statistics. The activities developed were applied to a class of 23 third-year high school students at the Ponche Verde State High School, located in the city of Sertão-RS, and lasted five meetings and 13 activity periods. Qualitative in nature, the research focused on presenting forms of thought, together with situations where triggers are used for the predominance of System 1 in decision-making. The proposal is evaluated using three instruments: a logbook filled out by the research teacher, activities carried out by the students, and a final questionnaire answered by the class. Analysis of the collected data indicates the viability of the proposal, as well as the importance of considering situations related to the two forms of thinking in the school context, based on statistical and financial mathematics content. In this sense, the study shows that by bringing the topic into the classroom, students are more aware, critical, and attentive to the triggers frequently used in society that lead them to make decisions based on System 1. The study is accompanied by an educational product developed based on situations used in the classroom and which provides an opportunity to discuss the two systems of thinking proposed by Kahneman (2011). This educational product is available on the program's website (www.upf.br/ppgecm) and on the EduCapes portal (http://educapes.capes.gov.br/handle/capes/747115 ).